Evaluating consumers' acceptability of laser-labeled apple fruit - Durga Khadka; Martin J. Talavera; Eleni D. Pliakoni; Logan L. Britton; Londa Nwadike; Manreet S. Bhullar (Future Foods)
Fresh produce is traditionally labeled with plastic Price LookUp (PLU) stickers that are environmental contaminants and can easily detach during handling and disrupt traceability. The CO2 laser-labeling technology (LLT), an alternate method of produce labeling, has been gaining attention. However, the performance of this technology varies by produce, and consumer perception and acceptability remain understudied. The study evaluated consumers' perception and acceptability of the laser-labeled apple fruit that were purchased locally, laser-printed with a QR code, and coated with edible wax. A consumer study (N = 75) was conducted using 1) Apple with QR-code, 2) Apple with PLU plastic sticker, and 3) non-labeled control. Respondents received randomized treatment samples and completed questionnaires. The study revealed that QR-code labels were less preferred than sticker labels and no labels. Overall liking, label liking, and purchase intent were significantly lower for QR-code labels. However, after providing information about the QR-code benefits, rankings for all labels became statistically similar. Despite 52 % of respondents preferring QR-code labels for their sustainability benefits, they were less likely to recommend them than sticker labels. Laser labeling technology has the potential for industrial application from the consumers' perspectives, and providing consumer education is crucial for its success.